National Vocational Qualifications in the Tourism and Hospitality Industry of Slovenia - Rok, Marija (European Journal of Multidisciplinary Studies, 2019)
Hardly anybody would agree that the labour market satisfactorily meets the needs of the tourism and hospitality industry (THI). The THI worldwide faces the shortage of skilled labour force and the Slovenian THI is no exception. The problem persists in spite of various recruitment measures of employers, e.g. engaging migrant workforce, student work, black market, etc. The first aim of the paper was to explore the workforce needs of the THI with an emphasis on its unmet demands. The desk research revealed the mismatch between the supply and demand of the workforce on lower levels. Since the system of the National vocational qualifications (NVQ) is presumed beneficial for deficiencies of the labour market the second aim of the article was to explore the current state of the NVQ system in Slovenia and the selection of the existing NVQs in the THI in order to find out whether the number and structure of awarded NVQ certificates improved structural imbalances on the TH labour market. The author came to the conclusion that all forms of lifelong learning might contribute to improve the qualification structure of the labour force in the country provided that the employers overcome their distrust of the credibility and quality of the NVQs.